Pendidikan Akhlak dalam Perspektif Kitab Bidayatul Hidayah - Wanto, Wanto (Journal of Islamic Education, 2024)
Imam Ghazali in the Bidayatul Hidayah Book discusses a lot about moral education in Islam which is based on theology from the Koran and Hadith. The aim of this research is to describe moral education from the perspective of the Bidayatul Hidayah Book. The type is qualitative research with library study techniques whose main source is the Bidayatul Hidayah book. The results of this research explain and describe moral education as an important part of personal and spiritual development in Islam. Apart from that, there are examples and guidelines on how the moral principles in the book can be applied in everyday life, including in the context of education